Implementation of Amaliyah Thoriqoh Naqsabandiyah Kholidiyah as an Effort to Increase Spiritual Intelligence at Darul Falah Amtsilati Islamic Boarding School - Rois, Abd Aziz; Rohman, Fathur (Al-Ulum: Jurnal Pendidikan Islam, 2025)
This research aims to explore the implementation of Thoriqoh Naqsyabandiyah Kholidiyah practices at the pesantren and their impact on the spiritual intelligence of its followers. A descriptive qualitative approach was employed, with data gathered through observation, in-depth interviews, and document analysis. Data analysis was conducted thematically to examine the implementation of thoriqoh practices, their effects on spiritual intelligence, and the challenges encountered. The findings reveal that Darul Falah Amtsilati Islamic Boarding School, under the guidance of KH. Taufiqul Hakim, not only imparts religious knowledge but also deepens spirituality through Thoriqoh Naqsyabandiyah Kholidiyah. The thoriqoh practices include bai’at (initiation), dhikr, suluk (spiritual retreat), and tawajjuhan (spiritual focus) to purify the heart and draw closer to Allah, with silent dhikr (dhikr khafi) serving as the primary method for enhancing spiritual awareness. Through this thoriqoh, followers experience an increase in spiritual intelligence, such as developing a clearer life vision, feeling the presence of Allah, and engaging in consistent dhikr. Many followers previously felt their lives lacked direction, but after practicing these rituals, they became more disciplined in worship, patient, empathetic, and found joy in serving others. Participation in the thoriqoh is not limited to students; it also extends to the wider community, who can maintain their spiritual practices consistently through access to thoriqoh programs, digital technology, and guidance from teachers and religious study groups.